2009
DOI: 10.1007/s00066-009-1973-0
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Tissue Radioprotection by Overexpression of the Copper-Zinc and Manganese Superoxide Dismutase Genes

Abstract: Overexpression of CuZnSOD and MnSOD in HPLF mediated an increase in clonogenic survival after irradiation compared to controls. In previous works, a lack of radioprotection in SOD-overexpressing tumor cells was observed. Therefore, the present results suggest that rAAV2 vectors are promising tools for the delivery of radioprotective genes in normal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…These results are more promising than the ones we could show using nimesulide, a cyclooxygenase-2 inhibitor, in combination with irradiation on HNSCC cells [3]. As a consequence, it would make sense to do further investigations on betulinic acid's capability in combination with other cancer treatment modalities in different types of tumor tissue and also investigating possible radioprotective abilities on normal tissue [22]. Figures 4a and 4b.…”
Section: Discussionmentioning
confidence: 78%
“…These results are more promising than the ones we could show using nimesulide, a cyclooxygenase-2 inhibitor, in combination with irradiation on HNSCC cells [3]. As a consequence, it would make sense to do further investigations on betulinic acid's capability in combination with other cancer treatment modalities in different types of tumor tissue and also investigating possible radioprotective abilities on normal tissue [22]. Figures 4a and 4b.…”
Section: Discussionmentioning
confidence: 78%
“…Given all the adverse complications, it is crucial to prevent or slow down the progress of dysphagia and trismus. Although investigators have reported that normal-tissue radioprotection could be achieved by gene therapy [22], only a few therapeutic strategies have proved to be effective for these sequelae. Rehabilitation exercises were recommended and believed to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…These radiation-induced late effects seem to be caused by chronic oxidative stress [21]. Mitigation or treatment of chronic radiation damage has been shown experimentally in multiple organ systems, with different pharmacological agents, like angiotensin-converting enzyme inhibitors, pentoxifylline and superoxide dismutase mimetics, or gene therapeutic strategies [17]. Unfortunately, the mechanistic basis for most of the experimental successes has not been established, and assessment of the utility of these agents for clinical use has been slow.…”
Section: Discussionmentioning
confidence: 99%